The Role of Thoracic Endovascular Aortic Repair (TEVAR) of Thoracic Aortic Diseases in Patients with Connective Tissue Disorders - A Literature Review - Harky,Amer (2020)
Abstract Objective: To review the currently available literature to define the role of thoracic endovascular aortic repair (TEVAR) in patients with connective tissue disorders (CTD). Methods: A comprehensive electronic database search was performed in PubMed, SCOPUS, Embase, Google scholar, and OVID to identify all the articles that reported on outcomes of utilizing TEVAR in patients with CTD during elective and emergency settings. The search was not limited to time or language of the published study. Results: All the relevant studies have been summarized in its correspondence section. The outcomes were analyzed in narrative format. The role of TEVAR has been elaborated as per each study. Currently, there is limited large cohort size studies outlining the use of TEVAR in patients with CTD. The use of endovascular repair in patients with CTD is limited due to progressive aortic dilatations and high possibility of further reinterventions at later stage of life. Conclusion: Open repair remains the gold standard method of intervention in young patients with progressive CTD, especially in the setting of acute type A aortic dissection. However, TEVAR can be sought as a reliable alternative in emergency setting of diseases involving the descending thoracic aorta; yet the long-term data needs to be published to support such practice.